2013
DOI: 10.1038/gim.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors and cancer screening among Californians with a family history of cancer

Abstract: Purpose: The purpose of this study was to compare health behaviors and cancer screening among Californians with and without a family history of cancer. Methods:We analyzed data from the 2005 California Health Interview Survey to ascertain cancer screening test use and to estimate the prevalence of health behaviors that may reduce the risk of cancer. We used logistic regression to control for demographic factors and health-care access.results: Women with a family history of breast or ovarian cancer were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 34 publications
4
34
2
Order By: Relevance
“…In other studies, status regarding having a cancer patient among family or relatives was found to affect early diagnosis behavior positively, increase knowledge on cancer, and provide improvement in healthy lifestyle behavior (26)(27)(28). Contrary our study, some studies in literature have found that status regarding having a cancer patient among family or relatives doesn't affect behavior regarding protection from cancer (20,(29)(30)(31)(32). It is pleasing that according to the findings of our study, students under genetic risk show positive behavior for protection from cancer.…”
Section: Does Familial History Of Cancer Affect the General Health Cocontrasting
confidence: 76%
“…In other studies, status regarding having a cancer patient among family or relatives was found to affect early diagnosis behavior positively, increase knowledge on cancer, and provide improvement in healthy lifestyle behavior (26)(27)(28). Contrary our study, some studies in literature have found that status regarding having a cancer patient among family or relatives doesn't affect behavior regarding protection from cancer (20,(29)(30)(31)(32). It is pleasing that according to the findings of our study, students under genetic risk show positive behavior for protection from cancer.…”
Section: Does Familial History Of Cancer Affect the General Health Cocontrasting
confidence: 76%
“…These results are alarming because an FHD is a predisposition for future development of chronic disease, and habitual physical activity should play an important role in mitigating disease occurrence, particularly among this at-risk population. 2,7,15,16 Thus, there is a need to increase awareness of the role physical activity plays in chronic disease prevention, alongside conveying the risks associated with having a family history of chronic disease, particularly in a first-degree relative.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,17,18 Although genetic predisposition plays a major role in disease development, unhealthy lifestyle behaviors are often "inherited" as well and clustered within families. 7 Current findings might be explained by the social contagion theory, which emphasizes the role that social ties play in the propagation of norms and behaviors, such as weight loss and gain, physical activity, and dietary intake. 19 For example, Christakis and Fowler, 20 examining a network of more than 12,000 individuals enrolled in the Framingham Offspring Study, found a 40% increase in the risk for development of obesity for those whose siblings became obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Although women's screening practices have been found to correlate with their families' history of breast cancer, the lifestyle risk factors seem to be similar to those of women with no family history of cancer. 10,11 Little information is available about the lifestyle habits of BRCA1/2 carriers after the disclosure of genetic test results. Preliminary findings have shown that women applying for genetic testing may have better health-related practices than members of the general population.…”
mentioning
confidence: 99%